Autoinflammatory disease with focus on NOD2-associated disease in the era of genomic medicine. (17th February 2019) - Yao, Qingping; Li, Ellen; Shen, Bo
Abstract: Systemic autoinflammatory diseases (SAIDs) represent a spectrum of genetically heterogeneous inflammatory disorders. Some SAID-associated genes are located in chromosome 16, including familial Mediterranean fever gene ( MEFV ) and nucleotide-binding oligomerization domain 2 [ NOD2 ] gene that are linked to Crohn's disease, Blau syndrome, and Yao syndrome. These disorders share overlapping clinical phenotypes, and genotyping is diagnostically helpful and distinctive. Using next generation sequencing in SAIDs, digenic variants or combinations of more genetic variants in different genes can be detected, and they may be related to the MEFV and NOD2 genes. These variants may contribute to heterogeneous phenotypes in an individual, complicating the diagnosis and therapy. An awareness of the clinical significance of the digenic or combined gene variants is important in the era of genomic medicine.